Diversifikasi Produk Pengolahan Ikan pada Kelompok Ibu Rumah Tangga Pengusaha Karamba Ikan Banyu Hirang, Desa Bangkal, Kecamatan Cempaka, Kota Banjarbaru, Kalimantan Selatan - Nooryantini Soetikno; Yuspihana Fitrial; Iin Khusnul Khotimah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Fishery product diversification activities can be used to overcome problems that are often experienced by fish cage entrepreneurs. If there is an excess harvest of fresh fish or the yield is forced to do due to sudden changes in water conditions (such as water pollution, excess capacity of the buyer, the death of fresh fish), the problem has not resolved so far. The purpose of this activity is to provide knowledge and skills for housewife of “karamba” businesspeople in the form of making presto of soft thorn carp and nugget of tilapia in Bangkal Village, Cempaka District, Banjarbaru City, South of Kalimantan. The method used in this activity is the survey, demonstration, and evaluation of the implementation of activities. The results of this activity were in the form of nuggets of tilapia and presto of soft thorn carp produced by housewives of businesspeople from Banyu Hirang Village in Bangkal Village as participants. In addition to its delicious taste, has a high protein nutritional value, these processed products can also sell as a source of household income.